Declínio motor em indivíduos com paralisia cerebral no início da transição para a vida adulta: fatores associados e implicações para a participação - Monteiro, Rayane Félix Lôbo (Universidade Federal de São Carlos, 2023)
Contextualization: As a result of improved health care, individuals with Cerebral Palsy (CP) have shown greater longevity, which makes it relevant to understand the biopsychosocial aspects related to their health at the beginning of the transition to adolescence and adult life. For this, two studies were developed aiming at. Study 1 was a systematic review that raised factors related to motor decline in adolescents and adults with CP. The results obtained from the 22 identified articles indicated that the factors age, pain, neuromusculoskeletal aspects, level of the Gross Motor Function Classification System (GMFCS), changes in gait parameters, history of surgeries, and mobility performance that seem to influence the motor decline or improvement of adolescents and adults with CP. Given the above, Study 2 was carried out, which aims to characterize the profile of functionality and disability of adolescents with CP in Brazil, identifying the prevalence of risk factors that influence the motor decline of this population and their impact on participation, in which were 69 adolescents with CP, with a mean age of 11 years, were evaluated cross-sectionally using the GMFCS instruments, Manual Skill Classification System (MACS), Participation and Environment Measure - Children and Young People (PEM-CY), Pediatric Assessment Inventory of Disability - Computerized Adaptive Test (PEDI-CAT), applied remotely. The results indicated that in the home section, the GMFCS and Age factors were associated with the involvement variable. The MACS was associated with the desire for change and the GMFCS factors and health services (private/private) were associated with the number of activities. In the school section, the age factor was associated with the frequency variable. MACS was associated with engagement, desire for change, and number of activities. In the community section, MACS was associated with the frequency dimension. MACS and topography factors were associated with involvement. In the desire for change dimension, MACS factors and rehabilitation services were associated. And in the number of activities, the MACS factor was associated. Thus, the study presents a contribution in terms of public health, being able to subsidize the construction and structuring of public policies aimed at adolescents and adults with CP, promoting the appreciation of these subjects for their skills and potential.
Motor decline in individuals with cerebral palsy at the beginning of the transition to adulthood: associated factors and implications for participation
Keywords: Paralisia cerebral; Transição para Assistência do Adulto; Classificação Internacional de Funcionalidade, Incapacidade e Saúde; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL